Нелинейная теория неавтономных многомерных электронно-волновых систем миллиметрового диапазона (усилители и умножители) - Одаренко, Е. Н.; Шматько, А. А. (Издательство "Радиотехника", 2007)
The multidimensional model of the nonlinear hybrid O-type beam-wave system has been developed. The multistage device with sheet electron beam is considered as an amplifier and frequency multiplier. The theoretical analysis of nonlinear processes is carried out on the basis of the self-consistent multidimensional theory for different input amplitude values. The main regularities of the beam-wave interaction in the hybrid amplifying systems with resonance and nonresonance sections of the interaction space are investigated. The numerical simulation of the frequency multiplication process in the two-stage device with the nonresonance electron beam modulator and resonance output stage with prolonged interaction is performed.
Keywords: неавтономная колебательная система; миллиметровый диапазон; приборы О-типа; многомерная нелинейная теория